2017
DOI: 10.1111/evo.13258
|View full text |Cite
|
Sign up to set email alerts
|

The evolvability of herkogamy: Quantifying the evolutionary potential of a composite trait

Abstract: Accurate estimates of trait evolvabilities are central to predicting the short-term evolutionary potential of populations, and hence their ability to adapt to changing environments. We quantify and evaluate the evolvability of herkogamy, the spatial separation of male and female structures in flowers, a key floral trait associated with variation in mating systems. We compiled genetic-variance estimates for herkogamy and related floral traits, computed evolvabilities, and compared these among trait groups and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 81 publications
4
45
0
Order By: Relevance
“…Interestingly, both studies detected rapid evolution of traits that exhibited greater-than-average evolvabilities. The increased rate of selfing in M. guttatus was associated with reduced herkogamy (anther-stigma separation), which appears to be a highly evolvable trait (Opedal et al, 2017;and see Results). Similarly, the evolvability of volatile concentrations in Brassica rapa, computed from the heritabilities reported by Zu et al (2016), was very high with a median of 32.3% (Table S3).…”
Section: Researchmentioning
confidence: 74%
See 2 more Smart Citations
“…Interestingly, both studies detected rapid evolution of traits that exhibited greater-than-average evolvabilities. The increased rate of selfing in M. guttatus was associated with reduced herkogamy (anther-stigma separation), which appears to be a highly evolvable trait (Opedal et al, 2017;and see Results). Similarly, the evolvability of volatile concentrations in Brassica rapa, computed from the heritabilities reported by Zu et al (2016), was very high with a median of 32.3% (Table S3).…”
Section: Researchmentioning
confidence: 74%
“…(5) Herkogamy was measured on a ratio scale as defined in Opedal et al . (), i.e. as absolute anther–stigma distance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies found herkogamy to have a strong genetic basis (e.g., Herlihy and Eckert 2007;Luo and Widmer 2013), and a comprehensive review concluded that the trait is typically highly heritable and evolvable (Opedal et al 2017). Moreover, the profound functional implications of sexual organ position Keller et al 2012Keller et al , 2014Keller et al , 2016) justify speculating about possible adaptive explanations for the existence of high-herkogamous plants.…”
Section: Simultaneous Effects On Number Of Seeds and Mating Mode Of Smentioning
confidence: 99%
“…In addition to exploring how selection has shaped floral changes that follow the mating system transition, we use the Qst-Fst approach to detect selection for increased selfing itself. In self-compatible morning glories, selfing rate is controlled by herkogamy (anther-stigma separation), a quantitative trait known to be evolutionarily labile in many species (Chang & Rausher, 1998;Duncan & Rausher, 2013a;Opedal, Bolstad, Hansen, Armbruster, & Pélabon, 2017). We therefore use the Qst-Fst framework to determine whether selection favored reduced herkogamy in I. lacunosa.…”
mentioning
confidence: 99%